PERAN EUROPEAN CENTER FOR CONSTITUTIONAL AND HUMAN RIGHTS (ECCHR) DALAM MENANGANI SEXUAL AND GENDER-BASED VIOLENCE (SGBV) DI SURIAH TAHUN 2020 - Muhammad Syachdan Maulana; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Sexual and Gender-Based Violence (SGBV) is a serious and prolonged case in Syria. This phenomenon also involves armed people and even people of high rank and position. The world's international organizations, both IGOs and NGOs, have tried to help solve the problem of violence based on gender. This paper will describe how the strategy of the European Center for Constitutional and Human Rights (ECCHR) was successful in punishing two Syrian officials who committed gross human rights violations. Qualitative research is applied to answer the strategy used by ECCHR through secondary data. Documents from books, official publications such as the ECCHR annual report, journals, twitter, and articles from news worthy of trust. The theory of the Transnational Advocacy Network from Margaret E. Keck and Kathryn Sikkink will be used to analyze the strategies applied. The results showed that the strategies of Information politics, Symbolic Politics, Leverage Politics and Accountability Politics had been used. ECCHR and its partners conduct criminal complaints in German courts using the principle of international jurisdiction. The ECCHR has successfully convicted two former Syrian officials involved in the Sexual and Gender-Based Violence incident.Keywords : Information politics, Symbolic Politics, Leverage Politics, Accountability Politics, European Center for Constitutional and Human Rights (ECCHR), Transnational Advocacy Networks (TAN), Sexual and Gender-Based Violence (SGBV).